EVALUASI PEMANFAATAN PENGGUNAAN LAHAN BERBASIS RENCANA POLA RUANG KOTA BAUBAU, PROVINSI SULAWESI TENGGARA - Fikril Fahmi; Santun R.P Sitorus; Ahmad Fauzi (TATALOKA, 2016)
The high rate of economic growth has encouraged the development of Baubau City in various sectors of life. It has implications on the increase in space requirements. Rapid changes in land use often deviate from the spatial plan (RTRW) that has been legalized. This study aimed to evaluate the appropriateness and consistency of the land use plan and to investigate factors affecting the suitability and consistency of the land use growth with the spatial plan. The analysis has used GIS, Balance of Land Resources, Factor Analysis, and Multiple Regression Analysis. Based on the analysis, there are three forms of inconsistency from the spatial plan of Baubau, as follows: inconsistencies in the spatial plan itself, inconsistencies with the laws and regulations, and inconsistency in the utilization of the land use plan. The results have shown that the level of consistency to the land use plan is medium. The factors affecting the deviation of land use pattern from the plan are the ease of getting to service centers, the improved welfare, and the accessibility.